Evaluation of retinal nerve fiber layer thickness parameters in myopic population using scanning laser polarimetry (GDxVCC) - Dada, Tanuj; Aggarwal, A; Bali, SJ; Sharma, A; Shah, BM; Angmo, D; Panda, A (Nepalese Journal of Ophthalmology, 2013)
Introduction: Myopia presents a significant challenge to the ophthalmologist as myopic discs are often large, tilted, with deep cups and have a thinner neuroretinal rim all of which may mimic glaucomatous optic nerve head changes causing an error in diagnosis. Objective: To evaluate the retinal fiber layer (RNFL) thickness in low, moderate and high myopia using scanning laser polarimetry with variable corneal compensation (GDxVCC). Subjects and methods: One hundred eyes of 100 emmetropes, 30 eyes of low myopes (0 to - 4 D spherical equivalent(SE), 45 eyes with moderate myopia (- 4 to - 8D SE), and 30 eyes with high myopia (- 8 to - 15D SE) were subjected to retinal nerve fiber layer assessment using the scanning laser polarimetry (GDxVCC) in all subjects using the standard protocol. Subjects with IOP > 21 mm Hg, optic nerve head or visual field changes suggestive of glaucoma were excluded from the study. The major outcome parameters were temporal-superior-nasal-inferiortemporal (TSNIT) average, the superior and inferior average and the nerve fibre indicator (NFI). Results: The TSNIT average (p = 0.009), superior (p = 0.001) and inferior average (p = 0.008) were significantly lower; the NFI was higher (P < 0.001) in moderate myopes as compared to that in emmetropes. In high myopia the RNFL showed supranormal values; the TSNIT average, superior and inferior average was significantly higher(p < 0.001) as compared to that in emmetropes. Conclusion: The RNFL measurements on scanning laser polarimetry are affected by the myopic refractive error. Moderate myopes show a significant thinning of the RNFL. In high myopia due to peripapillary chorioretinal atrophy and contribution of scleral birefringence, the RNFL values are abnormally high. These findings need to be taken into account while assessing and monitoring glaucoma damage in moderate to high myopes on GDxVCC. Nepal J Ophthalmol 2013; 5(9):3-8 DOI: http://dx.doi.org/10.3126/nepjoph.v5i1.7814